Sosialisasi Terhadap Orang Tua Pentingnya Pendidikan Bagi Anak di Lingkungan RT 08 Kelurahan Mandala Merauke - Sri Hanipah; Herrio Tekdi Nainggolan; Syahfitriani Br Ginting (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
The best approach to addressing this issue is necessary due to parents' lack of understanding about children's education and current needs. Therefore, it is imperative to provide services that seek to improve parents' understanding through socialization. This service was held to better inform parents of RT 08 Kelurahan Mandala Merauke about educational efforts. The participants in this service totaled 20 people, all of whom were parents of children in the school age range. The method of service carried out was mentoring with a lecture, discussion, and question and answer approach. The results of the service showed a positive influence on parents' perceptions of education for children. After the material was delivered, it was clear that parents' understanding increased. To increase parents' awareness of education for children, it is recommended that the activities carried out be continued and made into routine activities.